Interference of peritoneal dialysis fluids with cell cycle mechanisms - Büchel, Janine; Bartosova, Maria; Eich, Gwendolyn; Hackert, Thilo; Schaefer, Franz; Schmitt, Claus P. (Peritoneal dialysis international, 2015)
Introduction: Peritoneal dialysis fluids (PDF) differ with respect to osmotic and buffer compound, and pH and glucose degradation products (GDP) content. The impact on peritoneal membrane integrity is still insufficiently described. We assessed global genomic effects of PDF in primary human peritoneal mesothelial cells (PMC) by whole genome analyses, quantitative real-time polymerase chain reaction (RT-PCR) and functional measurements. Methods: PMC isolated from omentum of non-uremic patients were incubated with conventional single chamber PDF (CPDF), lactate- (LPDF), bicarbonate- (BPDF) and bicarbonate/lactate-buffered double-chamber PDF (BLPDF), icodextrin (IPDF) and amino acid PDF (APDF), diluted 1:1 with medium. Affymetrix GeneChip U133Plus2.0 (Affymetrix, CA, USA) and quantitative RT-PCR were applied; cell viability was assessed by proliferation assays. Results: The number of differentially expressed genes compared to medium was 464 with APDF, 208 with CPDF, 169 with IPDF, 71 with LPDF, 45 with BPDF and 42 with BLPDF. Out of these genes 74%, 73%, 79%, 72%, 47% and 57% were downregulated. Gene Ontology (GO) term annotations mainly revealed associations with cell cycle (p = 10-35), cell division, mitosis, and DNA replication. One hundred and eighteen out of 249 probe sets detecting genes involved in cell cycle/division were suppressed, with APDF-treated PMC being affected the most regarding absolute number and degree, followed by CPDF and IPDF. Bicarbonate-containing PDF and BLPDF-treated PMC were affected the least. Quantitative RT-PCR measurements confirmed microarray findings for key cell cycle genes (CDK1/CCNB1/CCNE2/AURKA/KIF11/KIF14). Suppression was lowest for BPDF and BLPDF, they upregulated CCNE2 and SMC4. All PDF upregulated 3 out of 4 assessed cell cycle repressors (p53/BAX/p21). Cell viability scores confirmed gene expression results, being 79% of medium for LPDF, 101% for BLPDF, 51% for CPDF and 23% for IPDF. Amino acid-containing PDF (84%) incubated cells were as viable as BPDF (86%). Conclusion: In conclusion, PD solutions substantially differ with regard to their gene regulating profile and impact on vital functions of PMC, i.e. on cells known to be essential for peritoneal membrane homeostasis.